KONSEP KESEHATAN MENTAL DALAM AL-QUR’AN - Nurun Nufus; Kambali (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
Mental health is an important part of human life, both from a psychological, social and religious perspective. Islam as a religion has discussed mental health in the verses of the Koran. Writing this article uses a literature study approach. The primary source for this writing is a book on religious psychology written by Prof. Dr. Ramayulis, and secondary sources come from tafsir Al-Misbah, Ibn Katsir and tafsir from ministries of religion, supporters and journals that have similar themes. The purpose of writing this article is to find out and describe the concept of mental health in Islam and the Koran. The benefit of this article is as a forum for increasing understanding of mental health in Islam and helping readers to apply Islamic teachings in everyday life. As a result, the Qur'an consists of verses about human potential in forming mental health.